Functional current collector with improved thermal conductivity, preparation method thereof, pole piece and battery
Patent Information
- Application Number
- CN202510535817.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-27
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-04-27
AI Technical Summary
[0003]传统的高分子材料虽然具有良好的机械性能和加工性,但其导热系数较低,难以满足现代高性能应用中对于快速散热的要求
[0037]本发明的高分子基膜层包括含有功能性填料的非多孔高分子膜层和其两侧的含有功能性填料的多孔高分子膜层,通过这种方式构建成三层三维复合导热网络复合聚合物膜,能够形成电荷转移效应以及减少层间空隙和界面热阻。
Smart Images

Figure CN120413684B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, specifically to a functional current collector with improved thermal conductivity, its preparation method, an electrode, and a battery. Background Technology
[0002] With the development of electric vehicles, portable electronic devices, and large-scale energy storage systems, the demand for high-performance batteries is constantly increasing. As a key component connecting electrode materials and external circuits, the current collector's performance significantly impacts the efficiency, safety, and lifespan of the entire battery system. Compared to traditional current collectors, functional current collectors based on polymer films (structure: metal layer + polymer film layer + metal layer) have attracted considerable attention due to their low cost, light weight, and high safety.
[0003] While traditional polymer materials possess excellent mechanical properties and processability, their low thermal conductivity makes them unsuitable for the rapid heat dissipation requirements of modern high-performance applications. Although functional current collectors have improved upon the problems of traditional metal foils to some extent, their thermal conductivity still needs improvement. Currently, the industry's efforts to improve the thermal conductivity of functional current collectors are generally limited. For example, some improved functional current collectors increase thermal conductivity by adding a small amount of thermally conductive filler, but due to the weak interfacial bonding between the filler and the matrix material, a large interfacial thermal resistance is often generated, hindering effective heat transfer and affecting the thermal conductivity of the final product. Summary of the Invention
[0004] The purpose of this invention is to provide a functional current collector with improved thermal conductivity, its preparation method, electrode, and battery, thereby solving the problem of heat conduction in the composite structure of the functional current collector.
[0005] To achieve the above objectives, the technical solution provided by the present invention is as follows:
[0006] This invention is achieved through the following technical solution:
[0007] The first aspect of this application provides a functional current collector with improved thermal conductivity, comprising a polymer base film layer and metal layers on both sides of the polymer base film layer;
[0008] The polymer-based membrane layer includes a non-porous polymer membrane layer and porous polymer membrane layers on both sides of the non-porous polymer membrane layer. Both the non-porous polymer membrane layer and the porous polymer membrane layer contain functional fillers and electron-donating groups.
[0009] Furthermore, the functional filler is AB. x An inorganic ionic compound, wherein A is a cation, B is an anion, and x is 1 to 3; the electron-donating group is an ether bond or an amide group.
[0010] Furthermore, the functional filler is selected from one or more of CaF2, MgF2, AlF3, SrF2, BaF2, LaF3, CeF3, PbF2, NaCl, and KCl.
[0011] Furthermore, the functional filler particles in the porous polymer membrane have a particle size of 30–70 nm, and the functional filler particles in the non-porous polymer membrane have a particle size of 200–600 nm.
[0012] Furthermore, the thickness of the polymer base film layer is 3-30 μm, wherein the thickness of the porous polymer film layer on both sides accounts for 10-20% respectively, and the thickness of the non-porous polymer film layer in the middle accounts for 60%-80%; the average pore size of the porous polymer film layer is 50-100 nm.
[0013] A second aspect of this application provides a method for preparing a functional current collector with improved thermal conductivity, comprising the following steps:
[0014] Preparation of the first polymer film layer:
[0015] 1.1 Melt-blending of polymer masterbatch, functional filler, additives and pore-forming agent;
[0016] 1.2 The melt blend is subjected to crystallization treatment;
[0017] 1.3 The crystallized product is dried.
[0018] 1.4 The dried product is melted, extruded, and cooled to form a shape;
[0019] 1.5 After cooling and molding, stretching is performed to form a film;
[0020] 1.6 Heat treatment is performed after film formation;
[0021] 1.7 Introducing electron-donating groups into the heat-treated polymer film;
[0022] Preparation of the second polymer film layer:
[0023] 2.1 Melt-blending of polymer masterbatch, functional filler, and additives;
[0024] Steps 2.2 to 2.7 are the same as steps 1.2 to 1.7, respectively;
[0025] Preparation of multilayer films by hot pressing:
[0026] 3.1 Stack the first polymer film layer, the second polymer film layer, and the first polymer film layer in sequence;
[0027] 3.2 A multilayer film is formed by hot pressing the first polymer film layer, the second polymer film layer, and the first polymer film layer;
[0028] Preparation of polymer-based membranes containing porous and non-porous polymer layers:
[0029] The multilayer film formed by hot pressing is immersed in a solvent that can dissolve the pore-forming agent, and then washed with water and dried to obtain a polymer base film with porous polymer film layers on both sides and a non-porous polymer film layer in the middle.
[0030] Metal layers are prepared on both sides of the polymer base film.
[0031] To optimize the above technical solution, the specific measures / limitations also include:
[0032] In steps 1.1 and 2.1, the mass percentages of the polymer masterbatch, functional filler, and additive are 89–98.9 parts, 1–10 parts, and 0.1–1 parts, respectively. In step 1.1, the polymer masterbatch, functional filler, and additive are first melt-blended, and then a pore-forming agent accounting for 10–50% of the total volume of the melt-blended material is added, followed by continued melt-blending. The melt-blending temperature in steps 1.1 and 2.1 is 270–300℃. The crystallization treatment temperature in step 1.2 is 160–180℃, and the treatment time is 20–100 min. The drying treatment temperature in step 1.3 is 140–170℃, and the treatment time is 120–240 min. The melt extrusion temperature in step 1.4 is 270–300℃.
[0033] Step 1.5 Stretching to form a film includes longitudinal stretching and transverse stretching. The stretching process includes: preheating at a temperature of 90–130°C; stretching ratio of 3:1–4:1; heat setting at a temperature of 160–200°C; and cooling at a temperature of 30–50°C. Step 1.6 Heat treatment after film formation involves heat treatment at a temperature of 130–170°C for 1–2 minutes. In the preparation of multilayer films by hot pressing, the first and second polymer film layers are preheated before stacking. The preheating treatment is performed at a temperature of 80–100°C for 10–15 minutes. In Step 3.2 Hot pressing, the hot pressing temperature is 120–160°C, the applied pressure is set to 5–20 MPa, and the holding time is 10–30 seconds.
[0034] A third aspect of this application provides an electrode that includes the aforementioned functional current collector with improved thermal conductivity.
[0035] A fourth aspect of this application provides a battery comprising the aforementioned electrode.
[0036] Compared with the prior art, the beneficial effects of the present invention are:
[0037] The polymer-based film layer of the present invention includes a non-porous polymer film layer containing functional fillers and porous polymer film layers containing functional fillers on both sides thereof. In this way, a three-layer three-dimensional composite thermally conductive network composite polymer film is constructed, which can form a charge transfer effect and reduce interlayer voids and interfacial thermal resistance.
[0038] This invention uses specific functional fillers as modified fillers for polymer membranes, and controls the addition characteristics of functional fillers, such as content and particle size, within a specific range to further optimize the thermal conductive network and improve the thermal conductivity of the composite polymer membrane.
[0039] The polymer-based film layer prepared by this invention has good thermal conductivity and mechanical strength, and the functional current collector prepared with this polymer-based film layer has good metal layer adhesion and fewer pore defects. Attached Figure Description
[0040] Figure 1 : A schematic diagram of the structure of the polymer base film layer of the present invention.
[0041] Figure 2 : A schematic diagram of the structure of the functional current collector of the present invention.
[0042] In the figure: 1-polymer base film layer, 2-metal layer, 1-1-porous polymer film layer, 1-2-non-porous polymer film layer. Detailed Implementation
[0043] The present invention will be further described in detail below through specific embodiments, but it should not be construed as limiting the scope of the subject matter of the present invention to the following embodiments. All technologies implemented based on the above content of the present invention fall within the scope of the present invention.
[0044] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, and the reagents, methods and equipment used are conventional reagents, methods and equipment in this technical field.
[0045] This invention provides a functional current collector with improved thermal conductivity, such as... Figure 1 As shown, it includes a polymer base film layer 1 and metal layers 2 on both sides of the polymer base film layer;
[0046] The polymer-based membrane layer includes a non-porous polymer membrane layer 1-2 and porous polymer membrane layers 1-1 on both sides of the non-porous polymer membrane layer. Both the non-porous polymer membrane layer 1-2 and the porous polymer membrane layer 1-1 contain functional fillers, and both the non-porous polymer membrane layer and the porous polymer membrane layer contain electron-donating groups.
[0047] The functional filler is AB xThe inorganic ionic compound is a type where A is a cation, B is an anion, and x is 1 to 3; preferably A is a larger cation and B is a smaller anion, and preferably the functional filler is a nano-inorganic compound with a similar crystal structure.
[0048] The electron-donating groups in both non-porous and porous polymer membranes are strong electron-donating groups, preferably ether bonds or amide groups.
[0049] In some embodiments, the functional filler is selected from one or more of CaF2, MgF2, AlF3, SrF2, BaF2, LaF3, CeF3, PbF2, NaCl, and KCl.
[0050] In some embodiments, the functional filler particles in the porous polymer membrane have a particle size of 30-70 nm, preferably 40-60 nm; the functional filler particles in the non-porous polymer membrane have a particle size of 200-600 nm, preferably 300-500 nm.
[0051] In some embodiments, the polymer base material of the polymer base film layer is selected from materials containing C=O groups and benzene ring groups, preferably polyethylene terephthalate (PET), poly(1,4-cyclohexanediol) terephthalate (PCT), polybutylene terephthalate (PBT), bisphenol A type polysulfone (PSU), polyphenylene ether sulfone (PAS), polyether sulfone (PES), polyethylene naphthalate (PEN), polyethylene isophthalate and polyarylate (PAR), aromatic polylactic acid (PLA), aromatic polycarbonate (PC), aromatic polyamide (PA), aromatic polymethyl methacrylate (PMMA), polyimide (PI), and other materials and their derivatives and copolymers, one or more of these.
[0052] In the functional current collector of the present invention, the total thickness of the polymer base film layer can be 1-50 micrometers. Since the thinner the composite polymer film, the higher the energy density of the functional current collector prepared with this film as the base film, but at the same time, the production difficulty and yield rate also need to be taken into account, the present invention preferably has a polymer base film layer thickness of 3-30 micrometers, wherein the thickness of the porous polymer film layers on both sides accounts for 10-20% respectively, and the thickness of the non-porous polymer film layer in the middle accounts for 60%-80%.
[0053] In the existing technology, enterprises often encounter the problem of pores in the process of manufacturing functional current collectors. That is, in the process of preparing functional current collectors using physical vapor deposition with polymer film as base film, the heat generated by atomic deposition cannot be quickly exchanged with the outside, which makes the prepared functional current collectors prone to pore defects.
[0054] This invention utilizes the charge transfer effect between nanoscale thermally conductive functional fillers and polymer films, and simultaneously employs pore-forming agents to construct three-dimensional thermally conductive pathways, forming a composite polymer film with a three-layer structure. The interaction between the functional fillers and the polymer film leads to a "self-assembly effect" at the interlayer interface, thereby promoting the orderly arrangement of polymer molecular chains and improving the thermal conductivity of the functional current collector made from this polymer base film layer.
[0055] The main mechanism of the charge transfer effect is as follows: The strong electron-donating groups impart a strong electronegativity to the benzene ring at the center of the polymer chain, while the cationic A from the functional filler... x+ The cationic groups from the porogen have a strong positive charge and can accept electron transfer from individual polymer chains. Therefore, functional fillers and porogens can form intermolecular charge transfer interactions with polymers to construct electron donor-acceptor complexes.
[0056] This invention adds a porogen during the preparation of the upper and lower polymer film layers of the polymer base film. This porogen can drive the nano-functional fillers to orient along the pore walls during the leaching process, promoting the formation of three-dimensional thermal conductivity pathways in the polymer film. The middle polymer film layer does not contain a porogen and features larger functional filler particle sizes. The large-particle functional filler nanosheets tend to have "face-to-face" contact, which can reduce interlayer voids and interfacial thermal resistance. This allows for a stronger charge transfer effect with the polymer molecules in the surface polymer film material, resulting in the ordered arrangement of polymer molecular chains and the construction of a continuous three-layer three-dimensional composite thermal conductivity network, thereby improving the thermal conductivity of the composite polymer film.
[0057] Verification has shown that the optimal solution is to use the functional filler particle size specified in this application. The particle size of the functional filler, as a small particle, cannot be set too small, nor as a large particle, it cannot be set too large. If the particle size is too large, it will fall off or cause scratches during friction. In addition, it will increase the melt viscosity of the polymer material and reduce its fluidity, thereby affecting the processing performance and molding effect. If the particle size of the filler is too small, it is easy to agglomerate, which will also affect its uniform dispersion in the polymer material matrix.
[0058] In this invention, although the pore-forming agent is removed during the subsequent impregnation process, a charge transfer effect is formed during preparation through the following mechanism:
[0059] (1) Interactions during the preparation stage: cations in the porogen (such as [BMIM] in 1-butyl-3-methylimidazolium tetrafluoroborate) + ) and cations such as Ca in functional fillers 2+ It undergoes charge transfer with electron-donating groups (such as ether oxygen or amide oxygen) in the polymer membrane to form an electron donor-acceptor complex;
[0060] (2) Structure retention effect: The impregnation process promotes the arrangement of functional fillers such as CaF2 nanosheets along the pore walls, while the hot pressing treatment fixes the ordered "crystalline phase" structure and maintains the pre-formed charge transfer network.
[0061] (3) Dynamic equilibrium: Even if the porogen is washed away, the residual interfacial effect and intermolecular forces can still maintain the stability of the charge transfer channel.
[0062] This invention also provides a method for preparing a functional current collector with improved thermal conductivity, comprising the following steps:
[0063] S1: Preparation of the first polymer film layer:
[0064] 1.1 Melt-blending of polymer masterbatch, functional filler, additives and pore-forming agent;
[0065] 1.2 The melt blend is subjected to crystallization treatment;
[0066] 1.3 The crystallized product is dried.
[0067] 1.4 The dried product is melted, extruded, and cooled to form a shape;
[0068] 1.5 Then stretch it into a film;
[0069] 1.6 Heat treatment after film formation;
[0070] 1.7 Introducing electron-donating groups into the heat-treated polymer film;
[0071] S2: Preparation of the second polymer film layer:
[0072] 2.1 Melt-blending of polymer masterbatch, functional filler, and additives;
[0073] The remaining steps are the same as steps 1.2 to 1.7;
[0074] S3: Hot pressing to prepare multilayer films:
[0075] 3.1 Stack the first polymer film layer, the second polymer film layer, and the first polymer film layer in sequence;
[0076] 3.2 A multilayer film is formed by hot pressing the first polymer film layer, the second polymer film layer, and the first polymer film layer;
[0077] S4: Preparation of polymer-based membranes containing porous and non-porous polymer membranes:
[0078] The hot-pressed multilayer film is immersed in a solvent that can dissolve the pore-forming agent, and then washed with water and dried to obtain a polymer base film layer.
[0079] S5: Prepare metal layers on both sides of the polymer base film.
[0080] In steps 1.1 and 2.1, the mass fractions of polymer masterbatch, functional filler, and additive are 89-98.9 parts, 1-10 parts, and 0.1-1 parts, respectively. If too little functional material is added, it will not improve the thermal conductivity of the polymer membrane, while adding too much will easily cause membrane defects and reduce the mechanical properties of the polymer membrane.
[0081] In step 1.1, the polymer masterbatch, functional filler and additives are melt-blended first, and then a pore-forming agent accounting for 10-50% of the total volume of the melted material is added to continue melt-blending.
[0082] The melting and blending temperature for steps 1.1 and 2.1 is 270–300°C. The mixture should be thoroughly mixed to ensure uniform dispersion.
[0083] In step 1.1, the pore-forming agent preferably accounts for 20%-40% of the total volume of the molten material.
[0084] In some embodiments, the porogen may be selected from one or more of the following: 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium hexafluorophosphate, 1-butyl-3-methylimidazolium trifluoromethanesulfonate, 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-butyl-3-methylimidazolium ethyl sulfate, 1-butyl-3-methylimidazolium diethylphosphonate, and 1-ethyl-3-methylimidazolium hydrosulfate.
[0085] The additives in this invention are mainly slip agents and antioxidants; the slip agent can be selected from one or more of pentaerythritol tetrastearate, calcium stearate and fatty acid amides; the antioxidant can be selected from hindered phenolic antioxidants, such as 2,6-di-tert-butyl-4-methylphenol, antioxidant 1010, antioxidant 1076 and one or more; the specific dosages can be determined and selected based on the experience of those skilled in the art and in conjunction with the experimental process.
[0086] In some embodiments, the polymer masterbatch in step 1.1 is first cleaned and then dried at 140-180°C for 4-8 hours to remove moisture and prevent the masterbatch from generating bubbles or degrading during the melting process; the intrinsic viscosity of the polymer masterbatch can be between 0.60 and 0.90 dL / g, preferably between 0.65 and 0.85 dL / g.
[0087] Step 1.2 The raw material can be crystallized in a crystallizer at a temperature of 160-180°C for 20-100 minutes. Crystallization improves the crystallinity of the polymer material and prevents adhesion during drying.
[0088] After crystallization, it needs to be dried again to remove any moisture that may be generated and to prevent the polyester from being oxidized during melt extrusion. The drying temperature in step 1.3 is 140-170℃ and the treatment time is 120-240 min.
[0089] Step 1.4 The dried mixture is fed into an extruder, where the temperature of the melt extrusion is 270-300℃. Impurities are filtered through a screen to ensure the purity of the melt. Then, the molten material extruded from the die is cast onto a casting roller and shaped by cooling treatment with the casting roller and water.
[0090] Step 1.5, film stretching, includes longitudinal stretching and transverse stretching. The stretching process includes: preheating at a temperature of 90–130°C; a stretching ratio of 3:1–4:1; heat setting at a temperature of 160–200°C; and cooling at a temperature of 30–50°C. The stretching process is illustrated below with examples, not limited to these:
[0091] Longitudinal stretching:
[0092] ① Preheating: The film formed before stretching needs to be preheated to above the glass transition temperature (Tg). The preheating conditions are: preheating temperature is 90-120℃.
[0093] ②Stretching: After preheating, the diaphragm is stretched longitudinally. The stretching process conditions are: stretching ratio of 3:1-4:1.
[0094] ③ Heat setting: After the diaphragm is stretched, it is heat set at a temperature of 160-200℃.
[0095] ④ Cooling: After heat setting, the diaphragm is cooled to a temperature of 30-50℃.
[0096] Lateral stretching:
[0097] ① Preheating: The diaphragm needs to be preheated before transverse stretching. The preheating conditions are: preheating temperature is 100-130℃;
[0098] ②Stretching: After preheating, the diaphragm is stretched laterally. The stretching process conditions are: stretching ratio of 3:1-4:1.
[0099] ③ Heat setting: After the diaphragm is stretched, it is heat set at a temperature of 160-200℃.
[0100] ④ Cooling: After heat setting, the diaphragm is cooled to a temperature of 30-50℃.
[0101] Step 1.6 The heat treatment after film formation is to perform heat treatment at a temperature of 130-170℃ for 1-2 minutes. The film after biaxial stretching needs to be heat treated at a higher temperature for a short time to eliminate internal stress, fix the molecular chain orientation, and improve dimensional stability.
[0102] Step 1.7 Introducing ether bonds or amide groups into the polymer, the specific steps are as follows:
[0103] (1) For amide groups grafted onto the surface of polyester polymers (PET, PBT, PEN, PCT):
[0104] ① Material pretreatment: The polyester film was immersed in a 5% NaOH ethanol solution and treated at 60℃ for 20 minutes to hydrolyze the surface ester groups and generate hydroxyl groups (-OH); it was then rinsed with deionized water and vacuum dried at 80℃. ② Amino grafting: A 5% ethanol solution of 3-aminopropyltriethoxysilane (APTES) was prepared, and the pretreated film was immersed in the solution and reacted at 80℃ for 2 hours to generate amino groups (-NH2) on the surface. The film was then washed with ethanol and dried. ③ Amide reaction: The film was immersed in a 5% maleic anhydride DMAc solution and reacted at 60℃ for 3 hours to generate surface amide groups (-CONH-).
[0105] (2) Polycarbonate (PC)
[0106] ① Partial hydrolysis: Immerse the PC film in a 1M KOH ethanol solution and treat it at 50℃ for 1 hour to generate surface hydroxyl groups (-OH); wash with ethanol and dry; ② Etherification reaction: Prepare a 10% epichlorohydrin DMAc solution; immerse the hydrolyzed film in the solution and react at 80℃ for 2 hours to introduce ether bonds (COC);
[0107] (3) Polymethyl methacrylate (PMMA)
[0108] ① Copolymerization reaction: Methyl methacrylate (MMA, 80 wt%) and acrylamide (AM, 20 wt%) are mixed, and 0.5 wt% AIBN initiator and toluene solvent are added; under nitrogen protection, the mixture is stirred at 60°C for 6 hours to generate PMMA-co-AM copolymer; ② Film formation and curing: The solution is cast into a film and dried at 80°C for 24 hours.
[0109] (4) Polysulfone (PSU, PES, PAS) type, optimized by heat annealing
[0110] ① Solution preparation: Dissolve PES particles in DMAc, add 10 vol% functional filler particles, and ultrasonically disperse for 2 hours; ② Thermal annealing treatment: Cast the solution into a film, gradually increase the temperature to 200℃, and anneal for 1 hour to promote the orderly arrangement of ether bond molecular chains.
[0111] In step S3, hot pressing to prepare a multilayer film, before stacking the polymer film layers, it is preferable to clean and preheat the first and second polymer film layers. The cleaning is done by using isopropanol or a special cleaning agent to clean the surface of each film layer to be pressed, ensuring that it is free of dust and oil. The preheating is done by preheating at 80-100°C for 10-15 minutes to remove moisture.
[0112] In step 3.2, during hot pressing, the hot pressing temperature is 120-160℃, the applied pressure is set to 5-20MPa, and the holding time is 10-30s; it is preferable to use a positioning clamp to fix the position during the hot pressing process.
[0113] Hot pressing can be used for hot pressing. Start the hot press to start heating and apply pressure. After the set time is reached, stop heating and start the cooling program to quickly cool the product to room temperature.
[0114] The multilayer film prepared by hot pressing is then wound up.
[0115] Step S4 involves dissolving the porogen in the polymer film using a solvent that can dissolve the porogen, while avoiding reaction with the polymer matrix; then, after washing and drying, the film is rewound.
[0116] In some embodiments, the solvent that can dissolve the porogen may be selected from one or more of dichloromethane, N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, 1,2-dichloroethane, sulfolane, hexafluoroisopropanol, etc.
[0117] The polymer base film layer produced by this method has an average pore size of 50-100 nm on both sides (upper and lower surface layers), which can be controlled to 60-80 nm through process adjustment and optimization. If the pore size is too small, the heat conduction channel becomes narrow, which limits the heat transfer efficiency. If the pore size is too large, it will weaken the overall structure of the polymer film and reduce its mechanical strength.
[0118] Step S5 involves preparing metal layers on both the upper and lower sides of the polymer base film. The metal layers can be prepared by physical vapor deposition, such as resistance heating vacuum evaporation, electron beam heating vacuum evaporation, laser heating vacuum evaporation, magnetron sputtering, chemical vapor deposition, or electroplating, or by any one or at least a combination of two of these methods.
[0119] To prevent oxidation of the prepared metal layer, an anti-oxidation layer can be provided on the surface of the metal layer on both the upper and lower sides to prevent the metal layer from being chemically corroded or physically damaged. The material of the anti-oxidation layer can be selected from one or more of nickel, chromium, tin, nickel oxide, chromium oxide, cobalt oxide, graphite, carbon nanofibers, graphene, and composites formed by organic matter and metal layer. The thickness of the anti-oxidation layer is between 10 and 100 nm, preferably between 20 and 60 nm. The preparation method of the anti-oxidation layer can be selected from impregnation, coating, magnetron sputtering, and electroplating.
[0120] Antioxidants can also be used to treat the surface of the metal layer. The antioxidants can be one or more inorganic antioxidants, such as chromates, dichromates, phosphates, etc., or one or more organic antioxidants, such as benzotriazole and its derivatives, fatty acids and their salts, amine compounds, etc.
[0121] The metal layer serves to conduct electricity or provide a barrier, and the metal layers on both the top and bottom sides are preferably made of the same material. The material of the metal layer can be selected from any one or a combination of at least two of the following: copper, copper alloy, titanium, titanium alloy, silver, silver alloy, aluminum, aluminum alloy, nickel alloy, nickel, or carbon.
[0122] The thickness of the single-sided metal layer is between 10-2000 nm, preferably 50-1500 nm.
[0123] The present invention also provides an electrode comprising the aforementioned functional current collector with improved thermal conductivity.
[0124] The present invention also provides a battery comprising the above-described electrode.
[0125] The technical solution of the present invention will be further described in detail below with reference to specific embodiments:
[0126] Example 1
[0127] Preparation of multilayer PET composite film:
[0128] The selected masterbatch is polyethylene terephthalate (PET), with an intrinsic viscosity of 0.7 dL / g; the selected functional filler is calcium fluoride (small particle size 40 nm, large particle size 300 nm); the selected additives include antioxidant 1010 and slip agent pentaerythritol tetrastearate; the selected porogen is 1-butyl-3-methylimidazolium tetrafluoroborate; and the selected solvent for dissolving the porogen is dichloromethane.
[0129] Preparation process:
[0130] 1. Raw material preparation: Selected high-purity PET masterbatch is cleaned and then dried at 140℃ for 4 hours;
[0131] 2. Melt Blending - Slicing: The A layer material of the upper and lower surfaces is prepared by heating, melting and mixing PET masterbatch, functional filler, additives and pore-forming agent, extruding and forming slices; the contents of PET masterbatch, functional filler calcium fluoride (particle size of 40nm), and additives (antioxidant 1010 and pentaerythritol tetrastearate) in the A layer material are 97.5%, 2% and 0.5% respectively. After the material is melted, 20% by volume of pore-forming agent 1-butyl-3-methylimidazolium tetrafluoroborate is added for melt blending; the contents of PET masterbatch, functional filler calcium fluoride (particle size of 300nm), and additives (antioxidant 1010 and pentaerythritol tetrastearate in a mass ratio of 1:2) in the middle B layer material are 97.5%, 2% and 0.5% respectively.
[0132] 3. Crystallization-drying: Place the PET slices in a crystallizer and dry them at 160°C for 30 minutes; then send the material to a drying tower and dry it at 160°C for 120 minutes.
[0133] 4. Melt extrusion: The dried PET raw material is fed into the extruder and melted at 290°C. Impurities are filtered through a screen to ensure the purity of the melt.
[0134] 5. Casting: The molten polyester material extruded from the die head flows onto the casting roller, and is formed by the casting roller and water cooling treatment to form a 32μm thick casting sheet;
[0135] 6. Longitudinal stretching: First, the casting is preheated at 100°C before stretching. Then, it is stretched longitudinally with a stretching ratio of 4:1. After stretching, the film is heat-set at 170°C. Finally, it is cooled and formed at 35°C.
[0136] 7. Lateral stretching: First, the casting is preheated at 100℃ before stretching. Then, it is stretched laterally with a stretching ratio of 4:1. After stretching, the film is heat-set at 170℃. Finally, it is cooled and formed at 40℃.
[0137] 8. Heat treatment: The biaxially stretched PET film needs to be heat-treated at 150℃ for 1 minute to eliminate internal stress;
[0138] 9. Surface grafted amide groups:
[0139] ① Material pretreatment: The polyester film was immersed in a 5% NaOH ethanol solution and treated at 60℃ for 20 minutes to hydrolyze the surface ester groups and generate hydroxyl groups (-OH); it was rinsed with deionized water and dried under vacuum at 80℃; ② Amino grafting: A 5% ethanol solution of 3-aminopropyltriethoxysilane (APTES) was prepared, and the pretreated film was immersed in the solution and reacted at 80℃ for 2 hours to generate amino groups (-NH2) on the surface; it was washed with ethanol and dried; ③ Amide reaction: The film was immersed in a 5% maleic anhydride DMAc solution and reacted at 60℃ for 3 hours to generate surface amide groups (-CONH-);
[0140] 10. Winding: After heat treatment, the film is cooled by air in the platform area and then enters the winding system through the traction system to wind the film, thus preparing a 2μm thick A-layer film;
[0141] The steps for preparing the B-layer film are the same as those for preparing the A-layer film, except that no pore-forming agent is added to the material composition in the "melt blending-slicing" process, and a 6μm thick B-layer film is finally prepared.
[0142] 11. Hot pressing: Place the film prepared in step 9 in an oven and preheat it at 90°C for 12 minutes to remove moisture;
[0143] Then, the prepared polymer films are stacked neatly in the manner of layer A / layer B / layer A; the hot pressing temperature is 140℃, the pressure is 10MPa, the holding time is 20s, and the cooling program is started at the same time to rapidly cool the product to room temperature;
[0144] 12. Multilayer PET composite film:
[0145] The multilayer film prepared in step 11 was immersed in dichloromethane solvent, washed with water, dried in an oven at 70-80℃, and then rewound to obtain the final multilayer PET composite film. The average pore size of the A layer film on both sides is 70nm.
[0146] Preparation of functional current collectors:
[0147] Preparation of the metal layer: The prepared multilayer PET composite film was placed in a magnetron sputtering chamber. Using a Ni-Cr alloy with a purity of 99.99% as the target material and argon as the gas source, a 20nm thick underlayer was deposited on the upper and lower surfaces of the prepared multilayer PET composite film by magnetron sputtering. Then, the prepared film with the underlayer was placed in the magnetron sputtering chamber again. Using a Cu metal target with a purity of 99.99% and argon as the gas source, magnetron sputtering was performed to prepare an initial copper layer with a thickness of 50nm.
[0148] Subsequently, the prepared thin film with the underlayer and preliminary copper layer was placed in an electroplating apparatus to thicken the copper layer through electroplating. The main salt contents in the plating solution were 120 g / L copper sulfate, 120 g / L sulfuric acid, and 60 mg / L chloride ions. The contents of the brightener (sodium polydisulfide dipropane sulfonate), wetting agent (decynyl glycol polyoxyethylene ether), and leveling agent (polyethyleneimine alkyl compound) were 20 mg / L, 200 mg / L, and 5 mg / L, respectively. Electroplating thickening treatment was performed under a current density of 1.5 ASD, and the final thickness of the two metal layers was 1 μm.
[0149] Preparation of the antioxidant layer: After cleaning and drying the electroplated thickened film with cold air, it is placed in an aqueous solution of potassium dichromate (2 g / L) for 20 s (the thickness of the antioxidant layer is 100 nm). Then, after rinsing with water, it is dried in an oven at 60 ℃ to obtain the prepared functional current collector.
[0150] Example 2
[0151] It is basically the same as Example 1, except that the amount of functional filler added to the upper and lower A layers and the middle B layer is 5%.
[0152] Example 3
[0153] It is basically the same as Example 1, except that the amount of functional filler added to the upper and lower A layers and the middle B layer is 10%.
[0154] Example 4
[0155] It is basically the same as Example 1, except that the particle size of the functional filler in the upper and lower A layers is 50nm.
[0156] Example 5
[0157] It is basically the same as Example 1, except that the particle size of the functional filler in the upper and lower A layers is 60nm.
[0158] Example 6
[0159] It is basically the same as Example 1, except that the large particle size of the functional filler in the middle B layer is 400nm.
[0160] Example 7
[0161] It is basically the same as Example 1, except that the large particle size of the functional filler in the middle B layer is 500nm.
[0162] Example 8
[0163] It is basically the same as Example 1, except that the thickness of the single layer of the upper and lower A layers accounts for 10% of the total thickness of the composite film.
[0164] Example 9
[0165] It is basically the same as Example 1, except that the average pore size of the upper and lower A layers is 80nm.
[0166] Example 10
[0167] It is basically the same as Example 1, except that the functional filler in the composite membrane is magnesium fluoride.
[0168] Comparative Example 1
[0169] Compared with Example 1, the difference is that: no multilayer PET composite film was prepared. Instead, a 10μm PET film (without functional fillers) was prepared directly using ordinary methods as the base film. The subsequent steps of preparing the metal layer and the antioxidant layer on both sides were the same as in Example 1.
[0170] Comparative Example 2
[0171] It is basically the same as Example 1, except that the upper and lower A layers prepared do not contain pores.
[0172] Comparative Example 3
[0173] It is basically the same as Example 1, except that the amount of functional filler added to the upper and lower A layers and the middle B layer is 15%.
[0174] Comparative Example 4
[0175] It is basically the same as Example 1, except that the particle size of the functional filler in the upper and lower A layers is 20nm.
[0176] Comparative Example 5
[0177] It is basically the same as Example 1, except that the large particle size of the functional filler in the middle B layer is 800nm.
[0178] Comparative Example 6
[0179] It is basically the same as Example 1, except that the thickness of the single layer of the upper and lower A layers accounts for 40% of the total thickness of the composite film.
[0180] Comparative Example 7
[0181] It is basically the same as Example 1, except that the functional filler in the composite membrane is boron nitride.
[0182] Test Evaluation:
[0183] The performance of the polymer films provided in the above embodiments and comparative examples, as well as the functional current collectors prepared therefrom, was tested using the following specific test methods:
[0184] ① Thermal conductivity: The thermal conductivity of the polymer film prepared above was tested according to standard ISO 22007-3:2008.
[0185] ② Tensile strength and heat shrinkage rate: The tensile strength of the polymer film and functional current collector prepared above was tested in accordance with the standards GB / T 1040.3-2006 and GB / T 10003-2008.
[0186] ③ Adhesion between the polymer film and the metal layer in the functional current collector: A layer of 3M double-sided tape is adhered to a 1mm thick aluminum foil, the functional current collector is adhered on top of the double-sided tape, and a layer of ethylene-acrylic acid copolymer film (DuPont Nurcel 0903, 50μm thick) is covered on top of the functional current collector, and then a 1.3×10 5 N / m 2 The sample was hot-pressed at 120℃ for 10 seconds, cooled to room temperature, and cut into strips of 150mm×15mm. Finally, the ethylene-acrylic acid copolymer film of the sample strip was fixed to the upper clamp of the tensile testing machine, and the rest was fixed to the lower clamp. After fixing, the two were peeled at an angle of 180° and a speed of 100mm / min. The peel force value was tested, which is the adhesion force between the polymer film and the metal layer.
[0187] ④ Number of pore defects in functional current collectors: The prepared functional current collector sample is placed on a defect detection rewinding machine (an intelligent defect detection device equipped with a CCD) and its surface is scanned. The number of pore defects with a pore diameter of less than 100μm per unit area of functional current collector is counted.
[0188] Table 1. Performance test results of the composite membranes and functional current collectors prepared in each embodiment and the control example:
[0189]
[0190]
[0191] Test results show that:
[0192] Comparing Examples 1-3 and Comparative Example 3, it can be seen that as the amount of functional filler increases, the thermal conductivity of the composite film also increases, but if it exceeds the preferred range, the mechanical properties of the film will decrease; and when there is too much functional filler, the surface of the base film will become too rough or uneven, thereby reducing the adhesion.
[0193] As mentioned earlier, under the constraints of process requirements, the lower limit of small particle size cannot be too low, and the upper limit of large particle size cannot be too high. The particle size ranges of Examples 1 and 4-7 are all within the scope of the claims. As the particle size of small particles in the surface layer increases, the thermal conductivity decreases slightly because the functional filler with small particle size in the surface layer is more evenly dispersed and has a better thermal conductivity. However, when the range of the claims is exceeded, such as when the particle size of small particles is too small, the specific surface area of small particle filler increases significantly, the surface energy increases, and agglomeration is likely to occur. Within the particle size range of the claims, the particle size of large particles in the intermediate layer increases, and the thermal conductivity of the intermediate layer is better. However, if the particle size is too large, it may be difficult to disperse evenly, resulting in insufficient filler in local areas, which cannot form an effective thermal conduction path and will increase the interfacial thermal resistance.
[0194] In Comparative Example 4, the small particle size of the filler significantly increases the specific surface area and surface energy, making it prone to agglomeration. After agglomeration, the filler is unevenly distributed in the polymer matrix, forming local "island" structures that hinder the formation of a thermally conductive network, thus reducing thermal conductivity. In Comparative Example 5, the large particle size is too large and difficult to disperse evenly, resulting in insufficient filler in some areas and the inability to form an effective thermal conduction path. At the same time, the excessively large particle size increases the interfacial thermal resistance because the contact area between the large particles and the matrix is relatively small, thereby reducing the overall thermal conductivity.
[0195] Comparing Example 1 and Comparative Example 1, it can be seen that the composite film prepared by the scheme of the present invention has significantly improved thermal conductivity, and other indicators such as thermal shrinkage rate and mechanical properties also show good performance.
[0196] Comparing Example 1 and Comparative Example 2, it can be seen that the composite membrane prepared by the scheme of the present invention has better performance than the composite membrane without pores due to the presence of pores on both the upper and lower surfaces.
[0197] A comparison of Example 1 and Comparative Example 6 shows that if the porous polymer membrane layers containing functional fillers on both sides are too thick, the tensile strength will be reduced too much, and the product will be unusable.
[0198] Boron nitride in Comparative Example 7 is a covalent compound, while the compound in this invention is an ionic compound. Covalent compounds cannot undergo charge transfer with electron-donating groups (such as ether oxygen or amide oxygen) in polymers to form electron donor-acceptor complexes.
[0199] A comparison of the embodiments of the present invention and the comparative examples shows that the solution of the present invention can also achieve better metal layer adhesion and fewer pore defects.
[0200] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any simple modifications, equivalent substitutions, and improvements made by those skilled in the art to the above embodiments without departing from the scope of the technical solution of the present invention, based on the technical essence of the present invention, shall still fall within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a functional current collector with improved thermal conductivity, characterized in that, Includes the following steps: Preparation of the first polymer film layer: 1.1 Melt-blending of polymer masterbatch, functional filler, additives and pore-forming agent; 1.2 The melt blend is subjected to crystallization treatment; 1.3 The crystallized product is dried. 1.4 The dried product is melted, extruded, and cooled to form a shape; 1.5 After cooling and molding, stretching is performed to form a film; 1.6 Heat treatment is performed after film formation; 1.7 Introducing electron-donating groups into the heat-treated polymer film; Preparation of the second polymer film layer: 2.1 Melt-blending of polymer masterbatch, functional filler, and additives; Steps 2.2 to 2.7 are the same as steps 1.2 to 1.7 respectively; Preparation of multilayer films by hot pressing: 3.1 Stack the first polymer film layer, the second polymer film layer, and the first polymer film layer in sequence; 3.2 A multilayer film is formed by hot pressing the first polymer film layer, the second polymer film layer, and the first polymer film layer; Preparation of polymer-based membranes containing porous and non-porous polymer layers: The multilayer film formed by hot pressing is immersed in a solvent that can dissolve the pore-forming agent to obtain a polymer base film with porous polymer film layers on both sides and a non-porous polymer film layer in the middle. Metal layers are prepared on both sides of a polymer-based film. In steps 1.1 and 2.1, the mass percentages of the polymer masterbatch, functional filler, and additive are 89-98.9 parts, 1-10 parts, and 0.1-1 parts, respectively. In step 1.1, the polymer masterbatch, functional filler, and additive are first melt-blended, and then a pore-forming agent accounting for 10-50% of the total volume of the melt-blended material is added, followed by continued melt-blending. The melt-blending temperature in steps 1.1 and 2.1 is 270-300℃. The crystallization treatment temperature in step 1.2 is 160-180℃. Step 1.6 The heat treatment after film formation is to perform heat treatment at a temperature of 130~170℃ for 1~2 minutes; in the preparation of multilayer films by hot pressing, the first polymer film layer and the second polymer film layer are preheated before stacking, and the preheating treatment is to preheat at a temperature of 80~100℃ for 10~15 minutes.
2. The method for preparing the functional current collector with improved thermal conductivity according to claim 1, characterized in that: The temperature for melt extrusion in step 1.4 is 270~300℃.
3. The method for preparing the functional current collector with improved thermal conductivity according to claim 1, characterized in that: Step 1.5 Stretching to form a film includes longitudinal stretching and transverse stretching. The stretching process includes preheating, stretching, heat setting and cooling. Step 3.2 During hot pressing, the hot pressing temperature is 120~160℃, the applied pressure is set to 5~20 MPa, and the holding time is 10~30s.
4. A functional current collector with improved thermal conductivity prepared by the method according to any one of claims 1 to 3, characterized in that: It includes a polymer base film layer and metal layers on both sides of the polymer base film layer; The polymer-based membrane layer includes a non-porous polymer membrane layer and porous polymer membrane layers on both sides of the non-porous polymer membrane layer. Both the non-porous polymer membrane layer and the porous polymer membrane layer contain functional fillers and electron-donating groups. The functional filler is selected from one or more of CaF2, MgF2, AlF3, SrF2, BaF2, LaF3, CeF3, PbF2, NaCl, and KCl; The thickness of the polymer base film layer is 3-30 μm, wherein the thickness of the porous polymer film layers on both sides accounts for 10-20% each, and the thickness of the non-porous polymer film layer in the middle accounts for 60%-80%.
5. The functional current collector with improved thermal conductivity according to claim 4, characterized in that: The functional filler is AB. x An inorganic ionic compound, wherein A is a cation, B is an anion, and x is 1 to 3; the electron-donating group is an ether bond or an amide group.
6. The functional current collector with improved thermal conductivity according to claim 4, characterized in that: The porous polymer membrane contains functional filler particles with a particle size of 30~70nm, and the non-porous polymer membrane contains functional filler particles with a particle size of 200~600nm.
7. The functional current collector with improved thermal conductivity according to claim 4, characterized in that: The average pore size of the porous polymer membrane is 50~100nm.
8. An electrode sheet, characterized in that: The present invention includes the functional current collector with improved thermal conductivity as described in any one of claims 4 to 7.
9. A battery, characterized in that: It includes the electrode sheet as described in claim 8.
Citation Information
Patent Citations
Current collector and preparation method thereof
CN114243028A
Composite current collector, electrode plate and lithium ion battery
CN118156512A
